VENTRICULAR STANDSTILL IN YOUNG MALE A RARE PRESENTATION OF GRAVES’ DISEASE A CHALLENGING DIAGNOSIS AND TREATMENT - Rana Kashif Riaz; Dr Aatika Habib; Hafsa Khalil (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Graves’ disease is an autoimmune disorder accounts for 80% hyperthyroidism, predominantly in females. Its association with cardiac arrhythmias such as atrial fibrillation, sinus tachycardia and supraventricular tachycardia DCM is well established. We report the case of 16 year old male with GD and rare cardiac complication Ventricular standstill or higher degree AVB that reports only less than 35 cases in entire literature make it unique, interesting and challenging case for diagnosis and management.